Beyond Rankings: Cultural Religious Foundations of Reputation in a Transforming Islamic University - Ahmad Fauzi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2022)
This study examines how institutional transformation in a pesantren-based Islamic higher education institution contributes to strengthening reputation, constructing a positive public image, and enhancing community attractiveness. Employing a qualitative case study design, data were collected through in-depth interviews, field findings, and institutional documentation, and analyzed using thematic analysis. The findings reveal four main themes. First, institutional transformation is interpreted as the restoration of institutional status and dignity through the historical narrative of “returning to university status.” Second, institutional reputation is primarily grounded in the cultural and religious capital of the pesantren, particularly public trust, the moral authority of kiai, scholarly traditions, and alumni networks, which extend beyond rational indicators such as rankings and facilities. Third, the institutional image is constructed through the tagline Kampus Pelopor Khoiru Ummah (Campus as a Pioneer of Khoiru Ummah), which is operationalized through public relations practices and character development programs rooted in Satlogi Santri (student) values and the Nine Noble Virtues of Santri. Fourth, institutional attractiveness is reinforced by emotional and religious bonds with the community, positioning higher education choice as a moral–spiritual decision. These findings indicate that managing change in Islamic higher education is more effective when institutional reforms are integrated with cultural–religious legitimacy embedded within the pesantren ecosystem